2020
DOI: 10.1111/liv.14632
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis as main determinant of portal hypertension through a restriction of hepatic sinusoidal area in a dietary rat nash model

Abstract: Background & Aims: Portal hypertension (PH) can be present in pre-cirrhotic stages, even in absence of fibrosis in non-alcoholic steatohepatitis (NASH) patients. Liver endothelial dysfunction (ED) has been shown as responsible for this effect in short-term dietary animal models. We evaluated the persistence of PH and underlying mechanisms in a long-term rat model of NASH. Methods: Sprague-Dawley rats were fed 8 or 36 weeks with control diet or high-fat high-glucose/fructose diet. Metabolic parameters, histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There is growing evidence that PH can occur in alcoholic fatty liver disease and NAFLD even in the absence of significant fibrosis/cirrhosis and that it correlates with the degree of steatosis [95][96][97][98][99][100][101]. Although the exact etiopathogenesis remains unclear, multiple hypotheses have been proposed.…”
Section: Metabolic Factorsmentioning
confidence: 99%
“…There is growing evidence that PH can occur in alcoholic fatty liver disease and NAFLD even in the absence of significant fibrosis/cirrhosis and that it correlates with the degree of steatosis [95][96][97][98][99][100][101]. Although the exact etiopathogenesis remains unclear, multiple hypotheses have been proposed.…”
Section: Metabolic Factorsmentioning
confidence: 99%
“…Impaired hepatic blood flow due to narrowing of the sinusoidal space has been demonstrated in rats fed choline-deficient diet, 26 New Zealand white rabbits fed high cholesterol diet, 27 the Zucker obese-rat model, 28 rats fed a methionine-choline deficient diet, 29,30 and in the rat model of human NAFLD using the cafeteria diet, 31 In all these reports, increased HVR developed in association with massive steatosis but without significant histological evidence of fibrosis, and without a significant increase in the expression of profibrotic genes, 32 Similarly, when steatohepatitis was induced in rats by high-fat glucose-fructose diet, increased PVP was demonstrated before significant fibrosis developed, 33,34 More recently, digital image analysis of hepatocellular fat and sinusoidal areas in the high-fat glucose-fructose diet model of NAFLD found an inverse correlation between vascular space and PVP. 35 Steatosis has also been associated with endothelial dysfunction and ineffective vasoregulation, implying that steatosis contributes to both the structural and dynamic components of increased HVR. [30][31][32] Clinical studies provide additional evidence for the development of portal hypertension in precirrhotic NAFLD (Table 1).…”
Section: Portal Hypertension Begins In Precirrhotic Nafld and May Pre...mentioning
confidence: 99%
“…endothelial dysfunction, imbalance in vasoactive substances) 2 , 3 and structural sinusoidal disturbances secondary to fatty liver changes could promote PH, even in the absence of fibrosis. 4 , 5 Our group reported that steatosis was the main determinant of PH in a 36-week dietary NASH rat model. 5 The main mechanism was the architectural distortion of the sinusoid area caused by accumulation of lipid droplets and morphological changes in hepatocytes, which led to sinusoidal compression and increased intrahepatic vascular resistance ( Fig.…”
mentioning
confidence: 96%
“… 4 , 5 Our group reported that steatosis was the main determinant of PH in a 36-week dietary NASH rat model. 5 The main mechanism was the architectural distortion of the sinusoid area caused by accumulation of lipid droplets and morphological changes in hepatocytes, which led to sinusoidal compression and increased intrahepatic vascular resistance ( Fig. 1 C)…”
mentioning
confidence: 96%
See 1 more Smart Citation